Pendampingan Literasi Keagamaan Islam untuk Mendukung Pemulihan Mental dan Spiritual Pasien Rehabilitasi Napza - Lusi Puspasari; Dyah Ayu Kusuma Dewandaru; Rani Sabtelasari; Dete Konggoro (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Islamic religious literacy mentoring is a strategic effort to support the mental and spiritual recovery of NAPZA rehabilitation patients. Religious literacy not only focuses on increasing knowledge but also on strengthening the values of aqidah/tawhid, cultivating worship practices, and developing sustainable moral character as a foundation for behavioral change. This study aims to foster Islamic religious values and enhance recovery motivation among male clients at Rumah Bina Insani Rejang Lebong. This study uses the Asset Based Community Driven (ABCD) approach, which emphasizes the utilization of existing strengths and positive assets possessed by the clients and their rehabilitation environment. Data were collected through observation, direct interaction, and routine mentoring, then analyzed descriptively. The results show that integrating religious literacy through aqidah, worship practices, and moral development significantly supports the recovery process. The clients experienced an improvement in religious understanding, spiritual awareness, and the ability to internalize positive values in their daily activities. Moreover, they developed renewed motivation to change and rebuild a more stable, directed, and positive character. Thus, Islamic religious literacy mentoring is proven to contribute effectively to the mental and spiritual recovery of NAPZA rehabilitation patients.